Glucocorticoid receptors and depression. Issue 6524 (29th March 1986) - Whalley, L J; Borthwick, N; Copolov, D; Dick, H; Christie, J E; Fink, G
Abstract : The number of glucocorticoid receptor sites in lymphocytes was estimated and plasma cortisol concentrations measured in 17 depressed patients, 12 patients with chronic schizophrenia, and 31 healthy control subjects. The number of receptor sites was significantly lower in the depressed patients than in either the controls or the patients with chronic schizophrenia, but there were no differences between the groups in the dissociation constants of the glucocorticoid receptors or the plasma cortisol concentrations. When two control subjects were studied intensively over 28 hours a slight diurnal variation in the number of glucocorticoid receptors was detected. The lower numbers of glucocorticoid receptors in the lymphocytes of depressed patients may explain why such patients, who often have hypercortisolaemia, do not show the clinical features of excess production of cortisol.